Hungarian EFL Learners’ Language Attitudes: The Influence of American English on Non-Native Speakers’ Accent Preferences - Püski, Gyöngyi (AMERICANA E-journal of American Studies in Hungary, 2024)
This paper focuses on Hungarian EFL learners’ attitudes toward Hungarian-accented and native varieties of English, with a special focus on the impact of American English on Hungarian EFL learners’ accent preferences. The paper reports on the results of two pilot studies (prepared for the author’s dissertation-in-progress): one carried out with the participation of 10 English major and 10 non-English major students, and a subsequent one based on the previous study, with 25 English majors, all from the University of Szeged. The results of the first study show that the majority describe their accent as being closer to American English than to British English, while the verbal guise experiment indicates that the British guise is preferred in all ratings (on both solidarity and status), with the exception of non-English majors’ indicating that the American guise sounds ‘warmer’. The majority of non-English majors believe that Hungarian EFL learners want to emulate American English, while most English majors think that it is British English or both British and American English that can be regarded as accent models for Hungarian learners of English. The results of the second study highlight that some of the participants consider their accents to be a mixture of British and American features, which they see as a flaw. Those respondents who wish to ‘sound American’ attach positive connotations to being able to speak English with an American accent, such as having a higher level of English knowledge and having an easily intelligible accent. The results suggest that American English seems to enjoy covert prestige even among those respondents who prefer British English in all respects, and positive values seem to be attached to Hungarian EFL speakers’ having an American accent.